2015
DOI: 10.1007/s00737-015-0544-x
|View full text |Cite
|
Sign up to set email alerts
|

The association between diabetes and postpartum depression

Abstract: This study aims to estimate if diabetic women were more likely to experience postpartum depression symptoms than women without diabetes. This was a prospective cohort of women who received prenatal care at a hospital-affiliated prenatal clinic serving low-income women in Chicago, Illinois. For the primary analysis, women were divided by diabetes status (i.e., no diabetes or either gestational diabetes or pre-pregnancy diabetes). Postpartum depression was defined as a positive screen on the Patient Health Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…This confirms our interpretation of the existing literature, which, though obfuscated by variation in methods and study populations, overall is more supportive of a forward causation, such that pre‐existing depression predisposes women to develop GDM, rather than the reverse. This is in line with the majority of relevant studies which also found no association of GDM with the later development of perinatal depression . In those studies where GDM was reported to precede depression , excessive maternal weight gain and Caesarean delivery may have been important mediating factors.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This confirms our interpretation of the existing literature, which, though obfuscated by variation in methods and study populations, overall is more supportive of a forward causation, such that pre‐existing depression predisposes women to develop GDM, rather than the reverse. This is in line with the majority of relevant studies which also found no association of GDM with the later development of perinatal depression . In those studies where GDM was reported to precede depression , excessive maternal weight gain and Caesarean delivery may have been important mediating factors.…”
Section: Discussionsupporting
confidence: 88%
“…Conversely, the available studies examining GDM as a risk factor for postpartum depression have yielded more variable results. A number of studies have either not found an association , or else found that when a relationship is present, it is explained by adjustment for medical comorbidities . One previous case–control study of 81 matched pairs did reveal a strong association between GDM and PPD that was robust to adjustment for confounders .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the above findings being in line with our observations, five other studies have found no associations between GDM and PPD/PPDS (Huang et al, 2015;Kim et al, 2005;Liu and Tronick, 2013;Meltzer-Brody et al, 2017;Miller et al, 2016). However, it is notable that the only one of these five studies to specify the diagnostic criteria for GDM used the two-step method recommended by the American Diabetes Association (Huang et al, 2015).…”
Section: Comparison With Previous Literaturesupporting
confidence: 79%
“…Racial disparities may also play a role, with Hispanic populations less likely than Caucasian populations to display this association 79,81 . Conversely, the available studies examining GDM as a risk factor for postpartum depression have either not found an association 75,82 or else found that when a relationship is present, it is explained by adjustment for medical comorbidities 83,84 . Gestational weight gain and Caesarean delivery, both complications of GDM, were particularly strongly associated with postpartum depressive symptoms 83 , suggesting that increases in body weight may be an important mediator in those cases where GDM does predate depressive symptoms.…”
Section: Inflammatory Mediators: Parallels Between Gestational Diabetmentioning
confidence: 96%